2017
DOI: 10.1002/cbdv.201700061
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sugar and Polyphenolic Diversity in Floral Nectar of Different ‘Oblačinska’ Sour Cherry Clones

Abstract: 'Oblačinska' sour cherry, an autochthonous cultivar, is the most planted cultivar in Serbian orchards. Since fruit trees in temperate zone reward insects by producing nectar which 'quality' affects the efficiency of insect pollination, the aim of this study was analyzing of sugars and polyphenolics in floral nectar of 16 'Oblačinska' sour cherry clones with different yielding potential. The contents of sugars and sugar alcohols were analyzed by ion chromatography, while polyphenolic profile was established usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…An Accela liquid chromatography (LC) system connected to a linear ion trap-Orbitrap hybrid mass spectrometer (LTQ OrbitrapXL, Thermo Fisher Scientific) with heated electrospray ionization (HESI) was used for the identification of flavonoid glycosides in bee-pollen samples. Chromatographic separation and mass spectrometry parameters were same as previously reported by Guffa et al [26].…”
Section: Uhplc-ltq Orbitrap Msmentioning
confidence: 99%
“…An Accela liquid chromatography (LC) system connected to a linear ion trap-Orbitrap hybrid mass spectrometer (LTQ OrbitrapXL, Thermo Fisher Scientific) with heated electrospray ionization (HESI) was used for the identification of flavonoid glycosides in bee-pollen samples. Chromatographic separation and mass spectrometry parameters were same as previously reported by Guffa et al [26].…”
Section: Uhplc-ltq Orbitrap Msmentioning
confidence: 99%
“…During the first day, we randomly assigned each bee to one of two treatments: (i) 20 µl of 1 mol l −1 sucrose solution twice a day or (ii) 20 µl of 1 μmol l −1 rutin (600 ppb, 12 ng per bee; Sigma-Aldrich R5143) solution dissolved in 1 mol l −1 sucrose solution twice a day. This dosage of rutin (determined after L. M. García, J. J. Sutachan, C. F. Morantes-Ariza, V. Caicedo-Garzón, S. L. Albarracín and A.J.R., unpublished) is within or below the reported concentrations from the field, although there is enormous variation among plant species (1180 ppb in nectar reported by Guffa et al, 2017 ; Gullón et al, 2017 ). Bees received a total of six doses across three consecutive days.…”
Section: Methodsmentioning
confidence: 57%
“…The presence of chrysin in propolis and honey strongly suggests that many plant species accumulate chrysins in flowers, probably in the pollen and/or nectar [ 54 , 55 ]. Accordingly, we found that O. sotoanum accumulates high levels of glycosylated chrysins in flowers, reaching bulk levels of 10 mg/g FW.…”
Section: Discussionmentioning
confidence: 99%